Influence of the height correction in the reduction of wear in external spur gears - Moya Rodríguez, Jorge L. (2008)
External spur gear drives are one of the most widely used in engineering applications. These transmissions can be enclosed in a casing and well lubricated, or work exposed to contaminating agents, as in the case of some transmissions in the construction industry, mining, agricultural machinery, etc. In these cases they are called open transmissions and their essential failure is the wear on the flank of the tooth, with subsequent fracture of the same. One of the most used ways to mitigate this failure is the use of high wear resistance materials or special lubricating greases. However, there is very little information in the gear literature about the influence of tooth geometry on the wear resistance of gear drives. In the present work, an analysis of the influence of tooth geometry on the wear resistance of spur external spur gear transmissions is made. The optimal values ​​of the toothing correction coefficient that minimize the relative slip between the teeth as a function of the number of teeth of the wheels are determined.